Advanced remote laser cutting of battery foils using an interference approach - Robert Baumann; Sabri Alamri; Alfredo I. Aguilar-Morales; Andrés F. Lasagni; Tim Kunze (Materials Letters: X, 2022)
This work demonstrates how an interference pattern can improve the performance of remote laser cutting of pure copper foils, making the cutting process effective even for a low power laser source. The proof of concept is carried out by using a nanosecond laser source with a pulse duration of 5 ns, coupled with a two-beam scanning interference setup, producing a spatial period of 12.5 µm. In the experiments, processing parameters as pulse-to-pulse distance, laser power and scanning speed are varied, to optimize the foil breakthrough and their effect on the generated material modifications are investigated. A comparison between the processing results employing the interference pattern and single beam with a Gaussian energy distribution is carried out. While the single beam process is not sufficient for cutting a 10 µm thin metallic foil, the interference treatment shows an improvement over 100%. In addition, only small spatter formations are detected, with average particle sizes of 1.75 ± 0.82 µm on the top side of the foil. The bottom side of a fully separated copper foil only depicts small spatter formations of less than 1 µm.